Experimental study designs to improve the evaluation of road mitigation measures for wildlife. (1st May 2015) - Rytwinski, Trina; van der Ree, Rodney; Cunnington, Glenn M.; Fahrig, Lenore; Findlay, C. Scott; Houlahan, Jeff; Jaeger, Jochen A.G.; Soanes, Kylie; van der Grift, Edgar A.
Abstract: An experimental approach to road mitigation that maximizes inferential power is essential to ensure that mitigation is both ecologically-effective and cost-effective. Here, we set out the need for and standards of using an experimental approach to road mitigation, in order to improve knowledge of the influence of mitigation measures on wildlife populations. We point out two key areas that need to be considered when conducting mitigation experiments. First, researchers need to get involved at the earliest stage of the road or mitigation project to ensure the necessary planning and funds are available for conducting a high quality experiment. Second, experimentation will generate new knowledge about the parameters that influence mitigation effectiveness, which ultimately allows better prediction for future road mitigation projects. We identify seven key questions about mitigation structures (i.e., wildlife crossing structures and fencing) that remain largely or entirely unanswered at the population-level: (1) Does a given crossing structure work? What type and size of crossing structures should we use? (2) How many crossing structures should we build? (3) Is it more effective to install a small number of large-sized crossing structures or a large number of small-sized crossing structures? (4) How much barrier fencing is needed for a given length of road? (5) Do we need funnel fencing to lead animals to crossing structures, and how long does such fencing have to be? (6) How should we manage/manipulate the environment in the area around the crossing structures and fencing? (7) Where should we place crossing structures and barrier fencing? We provide experimental approaches to answering each of them using example Before-After-Control-Impact (BACI) study designs for two stages in the road/mitigation project where researchers may become involved: (1) at the beginning of a road/mitigation project, and (2) after the mitigation has been constructed; highlighting real case studies when available. Highlights: High certainty studies on road mitigation effectiveness for wildlife are currently lacking. Experimentation improves knowledge on the influence of mitigation on wildlife. We set out the need for and standards of using an experimental approach to mitigation. We identify seven key questions about mitigation structures that remain unanswered. We provide experimental approaches to answering each question using BACI study designs.